Innovating climate and renewable energy education through deep learning and the engineering design process - Sarasdewi, Nadya Ursula (Proceedings of International Conference on Research in Education, 2025)
The rapid advancement of digital technology has transformed educational practices, demanding innovative approaches that foster deep learning and connect knowledge with real-world contexts. This study aims to develop a deep learning pedagogical model based on the Engineering Design Process (EDP) and a triple learning approach (meaningful, mindful, and joyful learning) within renewable energy projects in the digital era. An implementation approach was applied through contextual projects in which students designed and constructed renewable energy systems, engaging in continuous research, critical reflection, and problem-solving. The projects were carried out following the stages of the EDP, namely problem identification, ideation, planning, implementation, testing, and evaluation. The results indicate that the integration of EDP with a deep learning approach enhances active engagement, interdisciplinary conceptual understanding, and reflective awareness of energy sustainability issues. Students demonstrated critical, creative, and collaborative thinking skills through meaningful and enjoyable learning experiences. This model not only fosters ecological awareness but also develops scientific competencies relevant to the demands of 21st-century education. Therefore, the integration of EDP and the triple learning approach represents an educational innovation that supports transformative learning and aligns with the Sustainable Development Goals (SDGs).